A Critique of the Habermassian Theory of Communicative Action viewed through the Prism of the Post-operaist Theses - Gómez Villar, Antonio (2021)
This article revisits the post-operaist critique of Jürgen Habermas’s Theory of communicative action in light of the political issues prompted by the post-Fordist production system. It examines the post-operaist and Habermassian interpretation of Marx’s Grundrisse, focusing in particular on the concept of living labor. We also analyze the extent to which the hermeneutic potential of communicative action is annulled by shifting the problem from the ontological level to the ethical realm. Lastly, we argue that the duality between material labor and immaterial labor presented by post-operaism does not replicate the habermassian duality between communicative action and instrumental action.